Analysis of Instagram Social Media as Journalistic Activity in the @Kompascom Account - Bahagia Saragih; Muhammad Natsir (Randwick International of Education and Linguistics Science Journal, 2023)
In this digital era, the development of new media has given rise to a new form of journalism, namely digital journalism. Social media is used as a source of information. Journalist products are able to present information from journalists' coverage to be disseminated as news products to the public. This study discusses the use of social media Instagram as a means of spreading mass media news. The research aims to find out how Instagram is used as a means of disseminating news by media companies and how to implement practices in digital journalism on Instagram. The method used is descriptive qualitative with the @kompascom Instagram account object. The research findings show that Instagram is a means of publishing journalistic works that contain photos, captions, videos and news narratives.